Wireless Data Logger Suhu Multi Channel Menggunakan Labview - Siswo Wardoyo; Arya Prasetyo Habibie; Romi Wiryadinata (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Temperature is one of the physical quantities which are often used in control systems. The process of monitoring temperature in the form of a data logger is an important thing that is needed in the industry. This paper designs a wireless temperature data logger with multichannel input. Thermocouple is used as sensor input on this system. The results of this research indicate that the system is able to work wirelessly with a range of 300 meters until 800 m. Result of temperature measurement accuracy of the designed system is 99.419% or error temperature measurement against a reference temperature is 0.581%. Accuracy of voltage measurement towards Labview is 99.316% or error of 0.684%. The output file from data logger is file.tdms, which can be accessed by Microsoft Excel to be printed or processed further.